PENGGUNAAN BAHASA BALI DALAM KELUARGA KAWIN CAMPUR BALI-JAWA DI KELURAHAN KEROBOKAN KELOD, KECAMATAN KUTA UTARA, KABUPATEN BADUNG - Merita Sari, Ni Luh (Humanis; Volume 15. No.1. April 2016)
Bali as multilingual community is a community who can use more languages to communicate. One of the cause of multilingual community is a marriage among members of the community such as intermarry Balinese people with Javanese people in Kerobokan Kelod Village. This research aims is to know how to use Bali language in the intermarry Bali-Java family while communicating. Teory of sociolinguistic is use in this research. Methods and techniques use in this research consist of three, 1) observation and interview method for providing data, 2) method of qualitative and quantitative for data analysis , and 3) formal and informal method for presentation of data analysis. The result obtain from this research are 1) Bali language is more often use in intermarry family rather than other languages, especially when talking about religion, economy, education, health, and joking with family, 2) factors that make Bali language survive are loyalty to the Bali language, pride in the Bali language, awareness of the Bali language norms, Balinese community environment, and custom of Balinese community.
Keywords: language use, intermarry, language defense